End-of-life care preferences of older patients with multimorbidity: protocol of a mixed-methods systematic review. Issue 7 (6th July 2020) - Gonzalez-Gonzalez, Ana Isabel; Schmucker, Christine; Nothacker, Julia; Nguyen, Truc Sophia; Brueckle, Maria-Sophie; Blom, Jeanet; van den Akker, Marjan; Röttger, Kristian; Wegwarth, Odette; Hoffmann, Tammy; Gerlach, Ferdinand M; Straus, Sharon E; et al.
Abstract : Introduction: End-of-life care is an essential task performed by most healthcare providers and often involves decision-making about how and where patients want to receive care. To provide decision support to healthcare professionals and patients in this difficult situation, we will systematically review a knowledge cluster of the end-of-life care preferences of older patients with multimorbidity that we previously identified using an evidence map. Methods and analysis: We will systematically search for studies reporting end-of-life care preferences of older patients (mean age ≥60) with multimorbidity (≥2 chronic conditions) in MEDLINE, CINAHL, PsycINFO, Social Sciences Citation Index, Social Sciences Citation Index Expanded, PSYNDEX and The Cochrane Library from inception to September 2019. We will include all primary studies that use quantitative, qualitative and mixed methodologies, irrespective of publication date and language. Two independent reviewers will assess eligibility, extract data and describe evidence in terms of study/population characteristics, preference assessment method and end-of-life care elements that matter to patients (eg, life-sustaining treatments). Risk of bias/applicability of results will be independently assessed by two reviewers using the Mixed-Methods Appraisal Tool. Using a convergent integrated approach on qualitative/quantitative studies, we will synthesise information narratively and, wherever possible, quantitatively. Ethics and dissemination: Due to the nature of the proposed systematic review, ethics approval is not required. Results from our research will be disseminated at relevant (inter-)national conferences and via publication in peer-reviewed journals. Synthesising evidence on end-of-life care preferences of older patients with multimorbidity will improve shared decision-making and satisfaction in this final period of life. PROSPERO registration number: CRD42020151862.